Asymmetric droplet interface bilayers. - Hwang, W; Chen, M; Cronin, B; Holden, M; Bayley, H (2008)
In cell membranes, the lipid compositions of the inner and outer leaflets differ. Therefore, a robust model system that enables single-channel electrical recording with asymmetric bilayers would be very useful. We and others recently developed the droplet interface bilayer (DIB), which is formed by connecting lipid monolayer-encased aqueous droplets submerged in an oil-lipid mixture. Here, we incorporate lipid vesicles of different compositions into aqueous droplets and immerse them in an oil bath to form asymmetric DIBs (a-DIBs). Both alpha-helical and beta-barrel membrane proteins insert readily into a-DIBs, and their activity can be measured by single-channel electrical recording. We show that the gating behavior of outer membrane protein G (OmpG) from Escherichia coli differs depending on the side of insertion in an asymmetric DIB with a positively charged leaflet opposing a negatively charged leaflet. The a-DIB system provides a general platform for studying the effects of bilayer leaflet composition on the behavior of ion channels and pores.